Advances in automation and robotics research in Latin America : proceedings of the 1st Latin American Congress on Automation and Robotics, Panama City, Panama 2017 /: proceedings of the 1st Latin American Congress on Automation and Robotics, Panama City, Panama 2017. ([2017]) - Unknown
No abstract available